Mechanical behavior, failure mode, and transport properties in a porous carbonate. Issue 9 (12th September 2017) - Baud, Patrick; Exner, Ulrike; Lommatzsch, Marco; Reuschlé, Thierry; Wong, Teng‐fong
Abstract: We performed a systematic investigation of mechanical compaction, strain localization, and permeability in Leitha limestone. This carbonate from the area of Vienna (Austria) occurs with a broad range of grain sizes and porosity, due to changes in depositional regime and degree of cementation. Our new mechanical data revealed a simple relation between porosity and mechanical strength in both the brittle and ductile regimes. Increasing cementation and decreasing porosity led to a significant increase of the rock strength in both regimes. Micromechanical modeling showed that the dominant micromechanisms of inelastic deformation in Leitha limestone are pore‐emanated microcracking in the brittle regime, and grain crushing and cataclastic pore collapse in the ductile regime. Microstructural analysis and X‐ray computed tomography revealed the development of compaction bands in some of the less cemented samples, while more cemented end‐members failed by cataclastic flow in the compactant regime. In contrast to mechanical strength, permeability of Leitha limestone was not significantly impacted by increasing cementation and decreasing porosity. Our microstructural and tomography data showed that this was essentially due to the existence of a backbone of connected large macropores in all our samples, which also explained the relatively high permeability (in the range of 2–5 darcies) of Leitha limestone in comparison to other carbonates with significant proportion of micropores. Key Points: New triaxial experiments, petrophysical and CT data on Leitha limestone of porosity ranging from 18 to 31% Simple relation between porosity and strength over a wide range of pressures Compaction bands developed in less cemented samples of Leitha limestone